Dos vocabularis d'oficis valencians del segle XVII. G. Tarraça (1636) i V. Exulve (1643) - Colomina i Castanyer, Jordi (Caplletra. Revista Internacional de Filologia, 2015)
The article discusses the confrontation between these two Valencian vocabularies from 1636 and 1643, and analyzes the lexical features that are most relevant to the history of the language.